A templated ligand-driven assembly type pomegranate-like structure immunomagnetic bead and its preparation method and application
By modifying the affinity dopamine-modified silane reagent on dendritic mesoporous silica templates, multi-layer assembly of magnetic particles is solved, and the existing magnetic beads are difficult to take into account the immune response kinetics and magnetic separation efficiency under small sizes. Problem, high-performance pomegranate-like structure biomagnetic beads were obtained.
Patent Information
- Application Number
- CN202411237597.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-09-05
AI Technical Summary
While ensuring small size, existing magnetic beads are difficult to take into account efficient immune response kinetics and rapid magnetic separation, resulting in a reduced efficiency of immune detection.
Dental mesoporous silica is used as a template to modify the affinity dopamine-modified silane reagent to form a high-affinity surface. The binding site is used for dense assembly of magnetic particles, and the binding density and strength are improved through multi-layer assembly. , realize high-performance biomagnetic beads with pomegranate-like structure.
It realizes high-performance biomagnetic beads with excellent immune response kinetics and fast magnetic response under small size conditions. It is suitable for biomolecule separation and purification, and has a wide range of application prospects.
Smart Images

Figure CN118759170B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biological immune detection, and in particular relates to a templated coordination-driven assembly type pomegranate-like structure immunomagnetic bead and a preparation method and application thereof. Background Art
[0002] Chemiluminescence (CL) is the most important and accurate platform in immune response. It refers to the emission of light produced by chemical reaction process. In traditional plate chemiluminescence, the sample to be tested and the enzyme-labeled antibody or antigen are incubated with the modified antigen or antibody on the solid phase carrier. After washing, the antigen-antibody complex is obtained, and then the enzyme substrate is added to it. The enzyme specifically catalyzes the substrate to emit light. The disadvantages of this method are: due to the interface between the solid and liquid phases, the antibody is affected by the steric hindrance effect, and the antigen-antibody combination is slow. Therefore, a long incubation time is required to ensure that a sufficient amount of antigen-antibody can be solidified. Its sensitivity is low and non-specific adsorption will occur.
[0003] Compared with traditional plate-type chemiluminescence, magnetic microparticle chemiluminescence is to transplant the solid-phase capture substrate to the surface of colloidal-sized magnetic particles to achieve quasi-homogeneous immune reaction and can also be magnetically separated and enriched, which greatly improves the sensitivity and automation of immune reaction. It solves the technical bottleneck of traditional tube-type / plate-type solid-liquid interface chemiluminescence methods that are severely limited in reaction kinetics, and is a new type of homogeneous / quasi-homogeneous immune reaction system. Magnetic particles (i.e., biological magnetic beads) are the key raw materials and are crucial to the performance improvement of the overall detection reagent. Nano-sized magnetic particles are prone to superparamagnetism due to the particularity of their crystal structure, that is, they show strong magnetism under an external magnetic field. Since large-particle magnetic beads only have paramagnetism and ferromagnetism, controllable assembly with superparamagnetic critical size primitives less than 20 nm is the only way to construct magnetic bead immune carriers. Only in this way can the magnetic separation-resuspending characteristics under the conditions of external magnetic field action / removal, as well as high magnetic susceptibility and high saturation magnetization intensity, be maintained at the same time. At present, the development trend of Thermo Fisher magnetic beads is from 10 μm-6 μm-3 μm. Now Thermo Fisher's Dynabeads™ MyOne™ 1μm magnetic beads are developing towards improving chemical reaction kinetics (immunorecognition efficiency). However, due to the increase in specific surface area, the viscosity resistance of the solution is significantly increased, and magnetic separation is difficult to completely separate in a short time, which reduces the efficiency of immunoassay. Therefore, under the premise of ensuring a small size, significantly improving its superparamagnetic response is the key to balancing reaction kinetics and magnetic separation efficiency. From a structural perspective, it is difficult for current commercial magnetic beads and the magnetic bead structures reported in the literature to balance the size of less than 1 micron, and at the same time, the magnetic elements are filled with high density and high uniformity to achieve efficient immunodiagnosis.
[0004] The reported elementary self-assembly methods include template-free solvent evaporation induced self-assembly method, solid template assembly, porous polymer microsphere template assembly, etc. Among them, organic solvent evaporation induction is a classic self-assembly method. The advantages are that the low-boiling point solvent in the water-in-oil system is easy to remove, and the product has good phase stability in polar solvents. The disadvantages are that the particle size uniformity of the product is very poor, the porosity regulation mechanism is unclear, and it is difficult to prepare specific secondary structures such as hollow or porous structures, and the performance needs to be improved. In contrast, solid template assembly can provide excellent size and uniformity control, but currently only a layer of surface loading is achieved by using non-porous templates such as spherical silica. Cho et al. from Korea University used solid silica spheres as assembly templates and deposited a layer of surfactant-quantum dots (BMPA-QDs) or amino-functionalized surfactant-magnetic particles (BMPA-Fe3O4) solution alternately. Pang et al. utilized the swelling-contraction characteristics of cross-linked polystyrene microspheres (PS) to load magnetic particles or quantum dots to obtain magnetic signals and fluorescence intensity, and constructed a detection platform with high sensitivity and specificity for detecting Salmonella. However, the above process of assembling magnetic nanoparticles by in situ synthesis also has some disadvantages, such as the difficulty in controlling the size and shape of the obtained magnetic nanoparticles, especially the need for specific stabilizers to control the evolution of the geometry, surface and internal characteristics (such as charge density, type of dangling groups and porosity) of the particle growth process, the uncontrollable growth and loading density, the inability to assemble in multiple layers, the surface passivation of polyols and the inability to further chemically and biologically functionalize, and the more fatal disadvantage is that the template is solid and can only load a single layer of iron oxide particles near the surface, and the magnetic response is very limited. If the above template is replaced with a central radial channel, such as a dendritic silicon template and the coordination-driven three-dimensional filling of the internal space is developed, it is expected to achieve small size, high density, and high magnetic response performance.
[0005] According to the hard-soft acid-base (HSAB) theory, hard acids tend to form stable complexes with hard bases. The iron atoms in the structure of ferroferric oxide exist in different oxidation states (Fe 2+ and Fe 3+ ), and forms a complex oxide structure with oxygen atoms, which is regarded as a hard acid in the hard-soft acid-base (HSAB) theory. The two hydroxyl groups (-OH) in the catechol molecule act as ligands to provide lone pairs of electrons. Both functional groups can act as Lewis bases and act as hard bases in the hard-soft acid-base (HSAB) theory. According to the HSAB theory, hard ligands are more inclined to react with hard acids to form stable complexes. These lone pairs of electrons can form coordination bonds with the empty orbitals of metal ions. Fe 3+The ion has an empty d orbital and can accept the lone pair of electrons from the catechol molecule to form a coordination bond. The charge and electronic structure of the iron ion enable it to coordinate with multiple catechol molecules to form a multinuclear complex. Dopamine, as a bidentate ligand, can form multiple coordination bonds with the iron ion to enhance the stability of the complex. This chelation effect improves the thermal and chemical stability of the complex. There are currently several single dopamine-modified ligands, such as dopamine-polyethylene glycol carboxylamine / amine and amphoteric dopamine sulfonate. However, this monodentate ligand has a weak binding affinity to the surface of nanoparticles (NPs) and is easily replaced by biomolecules, resulting in decreased stability of the nanoparticles.
[0006] Based on the above technical problems, the present application grafts dopamine onto the silicon surface for organic phase affinity assembly of iron to construct an affinity, and at the same time, uses catechol as a modifying group to modify the polymer to obtain a catechol-grafted structure to construct a layer-by-layer brick and tile structure, which is of great significance for constructing this affinity organic phase porous template multilayer assembly.
[0007] The current layer-by-layer assembly is based on electrostatic interactions in the aqueous system. The assembly units with the same charge are subject to electrostatic repulsion in the aqueous system, which affects their assembly density. However, there is no report on the method of dense layer-by-layer stacking of magnetic particles by constructing a high-strength iron atom-ligand affinity in the organic phase. Summary of the invention
[0008] In view of the above technical problems existing in the prior art, the purpose of this application is to provide a templated coordination-driven assembly type pomegranate-like structure immunomagnetic beads and its preparation method and application. The present invention proposes to use dendritic mesoporous silica (dSi) as a template to synthesize a catechol-modified silane reagent with high affinity to iron atoms, and through silanization modification, grafted to the inside of the dendritic silicon template pores to form a high-affinity surface, providing binding sites for the dense assembly of the first layer of magnetic particles, thereby improving the functional element density of the entire three-dimensional space. The assembly of the second to fifth layers of magnetic particles is achieved by the organic phase layer-by-layer affinity assembly mediated by dopamine-grafted PIMA, and the binding density and strength are improved by forming a brick-and-tile structure. High-performance biological magnetic beads with a pomegranate seed structure that are multi-layered in the three-dimensional space (fast magnetic response) and small size (excellent immune response kinetics) are obtained.
[0009] The invention firstly synthesizes a macroporous dendritic silica (dSi) nano-template, and synthesizes and purifies oil-phase magnetic particles by adding ferric acetylacetonate and dodecanediol into anisole solvent, and using oleic acid and oleylamine as organic ligands. After that, a dopamine-modified silane reagent was synthesized and the surface was affinity modified by the dopamine-modified silane reagent (silane with a catechol group at the end) as a template for loading oil-phase magnetic particles for a layer of assembly. This layer provided a lot of binding sites, and its density determined the basic density of the entire three-dimensional space. Then, a PDA polymer was synthesized as an intermediate layer or PEI was synthesized as an intermediate layer. The magnetic particles and the PDA polymer or PEI were affinity assembled onto the silica template layer by layer through the organic phase in the oil phase, and transferred to the water phase through alkyl silane (octyltrimethoxysilane, OTMS) to obtain a water-dispersed magnetic particle-silica hydrophilic assembly and maintain a high loading density. Then, a dense silica protective layer was deposited overnight, and a silica layer with a thickness of about 10 nm was grown by the Stöber method to protect the assembly. At the same time, carboxylation was performed on this basis to obtain carboxylated magnetic beads. Finally, the carboxylated magnetic beads obtained by this method were used in a commercial chemiluminescence detection platform, and prolactin and testosterone were detected by the sandwich method and competitive method, respectively, demonstrating the enrichment and separation ability and universality of the magnetic beads in the field of biological detection.
[0010] The technical solution adopted by the present invention is as follows:
[0011] A method for preparing templated coordination-driven assembly type pomegranate-like structure immunomagnetic beads, using dendritic mesoporous silica dSi as a template, then grafting an affinity dopamine-modified silane reagent with a catechol group at the end to the dSi template pores to form a high-affinity surface, providing binding sites for the first layer of magnetic particles to be densely assembled, obtaining a dendritic silicon template modified by the catechol group, and then assembling the first layer of oil-phase magnetic particles 10s on the template, and then using a dopamine-grafted polymer PDA or PEI as a mediator to make the polymer PDA or PEI and the oil-phase magnetic particles 10s to form a high-affinity surface. Os is affinity assembled layer by layer on a silicon template in an organic solvent (preferably ethanol) to achieve layer-by-layer assembly of oil-phase magnetic particles IOs into multiple layers of IOs. Then, octyltrimethoxysilane (OTMS) is used to undergo a hydrolysis and condensation reaction on the surface of the microsphere assembly to achieve phase transfer of the microsphere assembly from the organic phase to the aqueous phase. Then, tetraethyl orthosilicate (TEOS) is hydrolyzed to grow a thin layer of silica by the Stöber method to improve the stability of the microsphere assembly. Then, 3-aminopropyltriethoxysilane is used to perform amino modification, and succinic anhydride is used to perform carboxyl modification to obtain carboxylated magnetic beads.
[0012] Furthermore, the preparation method of the affinity dopamine-modified silane reagent with a catechol group at the end comprises the following steps: adding dopamine and dihydro-3-[3-(triethoxysilyl)propyl]furan-2,5-dione to anhydrous DMF, ultrasonically homogenizing, and stirring at a speed of 100-250 rpm for 15-20 hours at room temperature to obtain the affinity dopamine-modified silane reagent; wherein the molar ratio of dopamine to dihydro-3-[3-(triethoxysilyl)propyl]furan-2,5-dione is 1.5-3:1, preferably 2.5-3:1.
[0013] Furthermore, the preparation method for grafting an affinity dopamine-modified silane reagent onto a dSi template includes the following steps: adding the dSi template and the affinity dopamine-modified silane reagent to ethanol, and adding ammonia water to adjust the solution to be alkaline, and the resulting mixture should be stirred and reacted at room temperature for 10-15 hours, wherein the ratio of the amount of the catechol group component in the affinity dopamine-modified silane reagent to the mass of the dSi template is 0.01-0.03:1, the unit of the amount of the substance is mmol, and the unit of mass is mg.
[0014] Furthermore, the preparation method of the dopamine-grafted polymer PDA comprises the following steps:
[0015] 1) Under nitrogen protection, poly(isobutylene-maleic anhydride) (PIMA) was heated and dissolved in DMF solvent;
[0016] 2) Dopamine hydrochloride is dissolved in DMF solvent, triethylamine is added, and the molar ratio of triethylamine to dopamine hydrochloride is 1-1.5:1. The solution becomes turbid, and is stirred at room temperature for 1-3 hours under a nitrogen atmosphere to activate dopamine, and then the formed triethylamine hydrochloride is removed by centrifugation to obtain a supernatant;
[0017] 3) adding the supernatant of step 2) dropwise to the solution containing PIMA of step 1), stirring overnight at 60-80°C, removing DMF under vacuum, adding deionized water to precipitate the product, washing with 0.5-2M hydrochloric acid solution, and then rinsing with deionized water, freeze-drying the solution, the product is a white powder, namely PIMA-DA, referred to as PDA;
[0018] The mass ratio of the PIMA in step 1) to the dopamine hydrochloride in step 2) is 1.5-3:1.
[0019] Furthermore, the first layer of load assembly of oil-phase magnetic particles IOs is carried out on the dendritic silicon template modified by catechol groups, and the process is as follows: take a toluene solution of oil-phase magnetic particles IOs, add the dendritic silicon template modified by catechol groups, ultrasonicate for 3-10 minutes to obtain a uniform mixed solution, then collect the precipitated product by centrifugation, and after the residual toluene solvent in the precipitate evaporates, a layer of IOs assembly dSi / IO1 is obtained; the mass ratio of the template to the oil-phase magnetic particles IOs is 1:1.5-2.0.
[0020] Furthermore, when assembling multiple layers of IOs on the silicon template, the assembly operation of each layer of IOs includes the following two steps:
[0021] S1 assembling and filling polymer PDA or PEI: adding an ethanol dispersion of polymer PDA or PEI to the upper layer assembly, wherein the mass ratio of the silicon template to the polymer PDA or PEI in the assembly is 1:0.5-2, preferably 1:1-1.2, and ultrasonically dispersing, then centrifuging and collecting the precipitated product, and washing with ethanol to obtain an intermediate layer assembly filled with PDA or PEI;
[0022] S2 performs the next layer assembly of IOs: adding the toluene solution of oil phase magnetic particles IOs to the intermediate layer assembly filled with PDA or PEI obtained in step S1, ultrasonicating for 3-10 minutes to obtain a uniform mixed solution, and then collecting the precipitated product by centrifugation to obtain the next layer assembly of IOs; wherein the mass ratio of the silicon template in the intermediate layer assembly filled with PDA or PEI to the oil phase magnetic particles IOs is 1:1-2;
[0023] Repeat the above steps S1-S2 1-4 times to assemble a total of 2-5 layers of oil phase magnetic particles 10s.
[0024] Further, a total of 4 layers of oil-phase magnetic particles 10s are loaded and assembled. When the second layer of oil-phase magnetic particles 10s is loaded and assembled, the mass ratio of the oil-phase iron oxide 10s to the silicon template dSi modified by the catechol group is 20-190%; when the third layer of oil-phase magnetic particles 10s is loaded and assembled, the mass ratio of the oil-phase iron oxide 10s to the silicon template dSi modified by the catechol group is 20-160%; when the fourth layer of oil-phase magnetic particles 10s is loaded and assembled, the mass ratio of the oil-phase iron oxide 10s to the silicon template dSi modified by the catechol group is 20-120%.
[0025] Further, the process of amino modification and carboxyl modification is as follows:
[0026] S1: Disperse the microsphere assembly in ethanol, add ammonia water and 3-aminopropyltriethoxysilane, stir and react at room temperature for 10-15 hours, then centrifuge and wash with ethanol to obtain a microsphere assembly with amino groups on the surface;
[0027] S2: Disperse the microsphere assembly with amino groups in an N,N-dimethylformamide solution containing succinic anhydride, stir and react for 3-5 hours, then centrifuge and wash with ethanol and water to obtain the carboxyl-modified microsphere assembly.
[0028] The present invention also discloses an application of a templated coordination-driven assembly type pomegranate-like structure immunomagnetic bead in a chemiluminescence detection platform, including an assembly process of a magnetic bead capture probe iSIS, wherein the magnetic bead capture probe iSIS includes a prolactin immunocapture probe or a testosterone immunocapture probe;
[0029] The assembly process of the prolactin immune capture probe includes the following steps: adding the immunomagnetic beads, i.e., carboxyl-modified microsphere assemblies, to a pH=6.0 PB buffer, adding Sulfo-NHS and EDC, and incubating in a shaker for 20-40 min; then centrifuging and collecting the product; resuspending the product in a pH=7.4 PBS buffer, adding mouse anti-prolactin monoclonal antibody 1 (mAb1), reacting at room temperature for 2-3 h, and then adding a final concentration of 5-20 mg / mL BSA for blocking for 1.5-3 h; then centrifuging and collecting the microspheres, counting them as iSIS magnetic beads, washing them with a pH=7.4 PBS buffer, and storing them in a pH=7.4 PBS buffer for refrigeration; and preparing a testosterone immune capture probe in the same manner using a mouse anti-testosterone monoclonal antibody 1 (mAb1);
[0030] The iSIS magnetic beads utilize chemiluminescent immunoassay technology to analyze and detect prolactin or testosterone.
[0031] The application of the present invention comprises detecting prolactin by sandwich immunoassay, the process being as follows:
[0032] 1) Prepare a series of prolactin solutions with different concentration gradients, with the prolactin concentration range of 0 uIU / mL-6000uIU / mL;
[0033] 2) The prolactin solutions of different concentrations prepared in step 1) are mixed with pH=7.4 PBS buffer containing iSIS magnetic beads, respectively, and incubated by shaking, and then acridinium ester-mouse anti-prolactin monoclonal antibody 2 (mAb2) is added, and the shaking incubation is continued, and then the product is separated by magnetic separation, and the product is washed with pH=7.4 PBS buffer, and then redispersed in pH=7.4 PBS buffer, and hydrogen peroxide with a final concentration of 0.4-1.0 mM and sodium hydroxide with a final concentration of 0.1-0.3 mM are added thereto, and the chemiluminescence intensity value of the immune complex is measured by a chemiluminescence immunoassay instrument; the concentration of prolactin is used as the horizontal axis, and the chemiluminescence value of the immune complex of the iSIS magnetic beads is tested as the vertical axis, a standard curve is prepared, and a linear regression equation is obtained by fitting; the iSIS magnetic beads are prolactin immune capture probes;
[0034] 3) When testing the prolactin solution sample, the prolactin solution sample, pH=7.4 PBS buffer containing iSIS magnetic beads, and acridinium ester-mouse anti-prolactin monoclonal antibody 2 (mAb2) are oscillated and incubated according to the test method of step 2), followed by magnetic separation and washing, and then redispersed in pH=7.4 PBS buffer. The chemiluminescence intensity value of the immune complex is measured by a chemiluminescence immunoassay instrument, and the value is substituted into the linear regression equation obtained in step 2) to infer the prolactin content in the prolactin solution sample.
[0035] The application of the present invention comprises detecting testosterone by a competitive method, and the process is as follows:
[0036] 1) Prepare a series of testosterone solutions with different concentration gradients, with the testosterone concentration range being 0-25 ng / mL;
[0037] 2) Testosterone solutions of different concentrations were mixed with pH=7.4 PBS buffer containing iSIS magnetic beads, acridinium ester-mouse anti-testosterone monoclonal antibody 2 (mAb2) was added and incubated with shaking, and then the product was separated by magnetic separation, and the product was washed with pH=7.4 PBS buffer and redispersed in pH=7.4 PBS buffer, and hydrogen peroxide with a final concentration of 0.4-1.0mM and sodium hydroxide with a final concentration of 0.1-0.3mM were added thereto, and the chemiluminescence intensity value of the immune complex was measured by a chemiluminescence immunoassay instrument; the chemiluminescence intensity value of the iSIS magnetic beads after detecting different concentrations of testosterone was recorded as B, and a blank group was set up, and the chemiluminescence intensity value of the iSIS magnetic beads after detecting pH=7.4 PBS buffer without testosterone was recorded as B0, and the testosterone concentration was used as the horizontal coordinate and the chemiluminescence intensity ratio B / B0 was used as the vertical coordinate to prepare a standard curve, and a regression curve was fitted; the iSIS magnetic beads are testosterone immune capture probes;
[0038] 3) When testing the testosterone solution sample, the testosterone solution sample, pH=7.4 PBS buffer containing iSIS magnetic beads, and acridinium ester-mouse anti-testosterone monoclonal antibody 2 (mAb2) are oscillated and incubated according to the test method of step 2), followed by magnetic separation and washing, and then redispersed in pH=7.4 PBS buffer. The chemiluminescence intensity value B1 of the immune complex is measured using a chemiluminescence immunoassay instrument, and the chemiluminescence intensity ratio B1 / B0 is calculated and substituted into the regression curve obtained in step 2), and the testosterone content in the testosterone solution sample can be inferred.
[0039] The beneficial effects achieved by the present invention are:
[0040] 1) The present invention proposes a new material construction strategy, using dendritic mesoporous silica (dSi) as a template, relying on the metal-ligand coordination effect, through the overlap of the assembly layers of the affinity molecule intermediate layer-hydrophobic functional unit, to achieve internal layer-by-layer self-assembly, forming high-performance biological magnetic beads with a pomegranate seed-like structure that has high magnetism, moderate sedimentation rate, high stability and can be reused multiple times. The unit filling density of this construction strategy is close to that of the classic organic solvent evaporation-induced self-assembly method, while retaining the incomparable advantages of highly controllable size and uniformity of the templated assembly method. This biological magnetic bead can be used to separate and purify biological molecules and has a wide range of application prospects. The focus to be protected is that this construction strategy has the characteristics of efficient self-assembly ability, simple preparation process, and strong scalability, while improving the performance of biological magnetic beads, and is expected to be widely used in the fields of biomedicine and molecular biology.
[0041] 2) Due to the synergistic effect of iron, the filling rate of commercial magnetic beads is very low, and they must be above the micron level to achieve effective response in a short time. If the reaction kinetics at the submicron level are to rise linearly, but its magnetic fraction is not enough, it is very important to have small size, high uniformity, and high magnetic response magnetic beads. Compared with the magnetic beads prepared by the organic solvent evaporation method, the magnetic beads based on the rigid silica nanosphere template of the present invention have the advantages of controllable size, small polydispersity index and strong repeatability; compared with the magnetic beads of in-situ growth magnetic particles, the present invention adopts the assembly mode of oil phase post-assembly, so that the proportion of loaded magnetic particles is controllable, and the magnetic particle load density can be increased by multi-layer assembly, and it has the advantage of post-modification; compared with the magnetic beads with solid silicon and polystyrene microspheres as templates, the dendritic mesoporous channel template of the present invention can achieve three-dimensional internal multi-layer filling, and achieve effective magnetic response under the condition of small size and good reaction kinetics. Compared with the mode of first transferring to the water phase and then assembling, the synthesis process of the magnetic beads of the present invention has fewer steps, which is conducive to the realization of industrial expansion. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1A It is a synthetic route and structural schematic diagram of the iSIS magnetic bead probe of the present invention;
[0043] Figure 1B This is a schematic diagram of the iSIS magnetic bead probe of the present invention used for chemiluminescence detection;
[0044] Figure 2 It is PDA dissolved in DMSO-d6 reagent 1 H NMR spectra;
[0045] Figure 3 It is a TEM image of the dendritic mesoporous silica nano-template and the products of each stage of layer-by-layer affinity loading of magnetic particles of the present invention;
[0046] Figure 4a is a graph showing the relationship between the magnetic particle loading rate ratio and the feed ratio of the characterization results of the one to four-layer oil phase assembly of the catechol group-modified silicon template of the present invention;
[0047] Figure 4b It is a photograph of the supernatant liquid and the dispersion liquid of the assembly during the one to four layer assembly process of the present invention.
[0048] Figure 5 are the hysteresis curves of Fe3O4 particles, dSi / IO4 four-layer assembly and SIS-COOH magnetic beads;
[0049] Figure 6a It is a distribution diagram of the hydrated particle size and polydispersity coefficient of the SIS magnetic beads of the present invention after magnetic separation and resuspension for 7 times and a photo of the dispersion thereof;
[0050] Figure 6b This is a graph showing the magnetic capture efficiency and absorbance value of the resuspension solution of SIS magnetic beads after magnetic separation and resuspension for 7 times, and a photo of the solution after magnetic separation;
[0051] Fig. 7A The experimental results of the probe iSIS of the present invention for chemiluminescence detection of testosterone are as follows: a. The standard curve of the luminescence intensity ratio B / B0 and the testosterone concentration of the magnetic beads for detecting testosterone by chemiluminescence competition method; b. The correlation curve of the testosterone concentration detection results of the magnetic beads for clinical samples and the detection results of the commercial Thermo Fisher Dynabeads™ MyOne™ 1μm magnetic beads;
[0052] Figure 7B a is the experimental result of the probe iSIS of the present invention for chemiluminescence detection of prolactin, b is the standard curve of the luminescence intensity and prolactin concentration of the magnetic beads for detecting prolactin by chemiluminescence sandwich method; a is the correlation curve of the prolactin detection concentration results of the magnetic beads for clinical samples and the detection results of the commercial Thermo Fisher Dynabeads™ MyOne™ 1μm magnetic beads.
[0053] Figure 8Photographs of the supernatant and the dispersion of the assembly body during the one to five-layer assembly process of the catechol group-modified silicon template of the present invention using PEI.
[0054] Fig. 9 A graph showing the relationship between the loading rate ratio of one to five layers of assembled magnetic particles and the feed ratio of the catechol group-modified silicon template assembled with PEI. DETAILED DESCRIPTION
[0055] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0056] In the embodiment of the present invention, the concentration of aqueous ammonia is 25-28%, and the mass concentration of hydrochloric acid is 36%.
[0057] The antibodies in the embodiments of the present invention are all from Meikang Biotechnology Co., Ltd.
[0058] Synthesis Example 1 of Carboxylated Magnetic Beads (SIS-COOH) (The synthesis route and structural schematic diagram of the iSIS magnetic bead probe of the present invention are shown in Figure 1A shown):
[0059] 1. Dendritic mesoporous silica (dSi) nano-template synthesis and surface modification channel process:
[0060] First, 0.136 g of triethanolamine was added to 50 mL of water and stirred at 80 °C for 30 minutes to fully disperse the triethanolamine. Then, a mixture of 0.760 g of hexadecyltrimethylammonium bromide and 0.567 g of sodium salicylate was added and the reaction continued for 1 hour, and then 8 mL of tetraethyl silicate was added and the resulting solution was gently stirred at 80 °C for 4 hours. The dSi produced by this method was collected by centrifugation, washed with ethanol three times, and then dispersed in a mixture of 50 mL of hydrochloric acid and 50 mL of methanol. The excess surfactant was extracted by stirring the mixture at 60 °C for 6 hours. The extraction process was repeated twice to obtain the dSi nanotemplate, and the dSi nanotemplate was dispersed in ethanol (the concentration of the dSi nanotemplate dispersed in ethanol was 2 mg / mL).
[0061] 2. Synthesis of affinity silanization reagent and template surface modification channel process:
[0062] Add 5 mmol of dopamine and 1.718 mmol of dihydro-3-[3-(triethoxysilyl)propyl]furan-2,5-dione to 5 mL of anhydrous DMF, mix well with ultrasound, stir slowly at room temperature for 18 h, and rotate at 180 rpm to obtain affinity silanization reagent (5 mL). Take 22.5 mL of ethanol suspension of dSi nanotemplate prepared in step 1) (containing about 45 mg of dSi nanotemplate), add 27.5 mL of ethanol, 625 μL of ammonia water, and add 2.19 mL of the above-mentioned dopamine-modified silanization reagent. The resulting mixture should be stirred at high speed for 12 hours at room temperature. After the reaction is completed, collect the white precipitate by medium-speed centrifugation, wash it with ethanol several times, and obtain a macroporous branched silica nanotemplate with catechol group-modified template channel, referred to as catechol group-modified silica template, which is dispersed in ethanol. The dispersion concentration of catechol group-modified silica template in ethanol is about 1 mg / mL.
[0063] 3. Synthesis and purification process of oil-phase ferroferric oxide nanoparticles (IOs):
[0064] To a 100-mL three-necked flask containing 10 mL of benzyl ether as a solvent, add 0.708 g of ferric acetylacetonate and 2.02 g of dodecanediol, add 4 mL of oleic acid and 4 mL of oleylamine as organic ligands, and heat to 50°C at a rate of 10°C / 5 min in an anhydrous and oxygen-free environment. Keep evacuating until the bubbles on the liquid surface disappear, refill with nitrogen to keep the reactants in an anhydrous and oxygen-free environment, set the end point temperature to 200°C and heat at a rate of 5°C / 1 min, react for 30 min with vigorous stirring at the end point temperature, then reset the end point temperature to 285°C and heat at a rate of 5°C / 1 min, keep the reaction temperature between 285-300°C, stir vigorously for 1.5 h, and then cool with air to terminate the reaction. When the solvent is cooled to room temperature, 15 mL of methanol is added to the solution as an anti-solvent to reduce the dispersibility of the magnetic particles. The solution is separated on a magnetic stand for 8 minutes. After the supernatant is removed, chloroform is used as a solvent to resuspend the magnetic particles. The precipitation-resuspension steps are repeated three times. Finally, the purified oil phase magnetic particles (ferroferric oxide, IOs) are dispersed in toluene for storage. The dispersion concentration of IOs in toluene is about 10 mg / mL.
[0065] 4. Synthesis and purification process of PDA intermediate layer polymer:
[0066] In a 50 mL three-necked round-bottom flask equipped with an addition funnel and a magnetic stir bar, 0.385 g of poly(isobutylene-maleic anhydride) (PIMA, molecular weight 6000 g / mol) was dissolved in 10 mL of DMF. The flask was purged with nitrogen for 10-15 min and the solution was heated to 70°C to obtain a solution containing PIMA.
[0067] In another vial, 0.7584 g dopamine hydrochloride (3.75 mmol) was dissolved in 2 mL DMF, and 556.8 μL of triethylamine was added. The solution became turbid and was stirred at room temperature for 2 hours under nitrogen atmosphere to allow dopamine to activate. The salt formed (triethylamine hydrochloride) was then removed by centrifugation, and the supernatant was added dropwise to the flask containing the PIMA solution prepared above. The reaction mixture was stirred at 70 ° C overnight. After removing DMF under vacuum, deionized water was added to precipitate the product, which was washed with 1M hydrochloric acid solution (3~4 times) and then rinsed with deionized water for the last time. After freeze-drying the solution, the product was a white powder, namely PIMA-DA, abbreviated as PDA polymer. The PDA polymer was dispersed in ethanol at a concentration of 10 mg / mL for use.
[0068] The PDA polymer prepared in step 4 of Example 1 was dissolved in DMSO-d6 reagent and then detected by nuclear magnetic resonance. 1 H NMR spectra are shown in Figure 2 As shown. Figure 2 It can be seen that multiple peaks at 6.4-6.7 ppm (from dopamine) and a peak around 0.9 ppm (from the methyl group of PIMA) were measured in the H NMR spectrum, confirming the successful synthesis of PDA.
[0069] 5. Layer-by-layer assembly of oil phase magnetic particles:
[0070] One-layer assembly of magnetic particles: Take 5 mL of the ethanol dispersion of the catechol group-modified silicon template prepared in step 2) (containing about 5 mg of the catechol group-modified silicon template), centrifuge, and blow dry. Take another 9 mg of iron oxide dispersed in toluene (magnetic particle feed ratio, i.e., the mass ratio of the oil-phase iron oxide IOs to the catechol group-modified silicon template dSi: 180%), add it to the silicon sphere, mix it by ultrasonication for 7 minutes, centrifuge, and remove the supernatant to obtain the precipitate, which is a one-layer assembly (dSi / IO1).
[0071] Two-layer assembly of magnetic particles: Take the above-mentioned one-layer assembly precipitate (dSi / IO1), blow dry, add 0.56 mL of PDA ethanol solution (10 mg / mL), add it to the assembly for ultrasonic dispersion, ultrasonic for 5 min, then wash once with ethanol and blow dry. Take another 9.5 mg of iron oxide dispersed in 0.95 mL of toluene (magnetic particle feed ratio 190%), add it to the assembly silicon sphere, ultrasonically mix for 7 minutes, centrifuge, and remove the supernatant to obtain a precipitate, which is the two-layer assembly (dSi / IO2).
[0072] Three-layer assembly of magnetic particles: Take the above two-layer assembly precipitate, blow dry, add 0.56 mL of PDA ethanol solution (10 mg / mL) to the assembly for ultrasonic dispersion, ultrasonic for 5 min, then wash once with ethanol and blow dry. Take another 8 mg of iron oxide dispersed in 0.8 mL of toluene (magnetic particle feed ratio 160%), add it to the assembled silicon sphere, ultrasonically mix for 7 minutes, centrifuge, and remove the supernatant to obtain the precipitate, which is the three-layer assembly (dSi / IO3).
[0073] Four-layer assembly of magnetic particles: Take the above three-layer assembly precipitate, blow dry, add 0.56 mL of PDA ethanol solution (10 mg / mL) to the assembly for ultrasonic dispersion, ultrasonic for 5 min, then wash once with ethanol and blow dry. Take another 6 mg of iron oxide dispersed in 0.6 mL of toluene (magnetic particle feed ratio 120%), add it to the assembled silicon sphere, ultrasonically mix for 7 min, centrifuge, and remove the supernatant to obtain the precipitate, which is the four-layer assembly (dSi / IO4).
[0074] The projection electron microscope images of the dSi template prepared in Example 1, the assembly after the dSi template is loaded with one layer of magnetic particles (the feed ratio is 180%), the assembly after the dSi template is loaded with two layers of magnetic particles (the feed ratio is 190%), the assembly after the dSi template is loaded with three layers of magnetic particles (the feed ratio is 160%), and the assembly after the dSi template is loaded with four layers of magnetic particles (the feed ratio is 120%) are shown respectively. Figure 3 As shown in a, b, c, d, and e, from Figure 3 a to Figure 3 From e in the figure, it can be seen that the loading amount of iron particles gradually increases, which is consistent with the gradual increase in the loading rate obtained in the experiment, confirming that the loading of magnetic particles is successful.
[0075] 6. Water phase conversion process and SiO2 coating:
[0076] Under ultrasonic conditions, the obtained four-layer assembly (dSi / IO4) was dispersed in 400 μL octyltrimethoxysilane (OTMS), and a solution of 30 mL methanol and 0.75 mL ammonia was added. Ultrasonication was continued for 30 minutes to catalyze the hydrolysis of silane in a weak alkaline environment. The resulting precipitate was collected by centrifugation, washed with a polar solvent methanol to remove excess unbound OTMS, and dispersed in a solution of 33 mL water and 50 μL ammonia. The mixture was then stirred at medium speed for 8 hours at room temperature to uniformly generate a silane protective layer, and finally a silane-modified magnetic particle assembly (dSi / IO4 / OTMS) was obtained. The obtained dSi / IO4 / OTMS was centrifuged to remove the supernatant and dispersed in 20 mL ethanol using ultrasound. Then, 5 mL water and 0.625 mL ammonia were added, and 10 μL TEOS was injected into it every 1 h for a total of 2 times, and the surface of dSi / IO4 / OTMS was coated with silica by the Stöber method. After 2 h, a total of 20 μL of TEOS was added, and the product was collected by centrifugation and washed three times with ethanol to remove excess TEOS to obtain a silica-coated magnetic particle nanosphere composite material (dSi / IO4 / Si, SIS), which was dispersed in ethanol at a concentration of 1.25 mg / mL for later use.
[0077] Figure 3 Figure f is a projection electron microscope image of the final product SIS, where a thinner silicon layer can be observed, proving the successful coating of silicon dioxide. Figure 3 It can be seen that the size of the SIS magnetic beads of the present invention is about 360 nm.
[0078] Figure 3 The products corresponding to the TEM images in the figure are: a. dendritic mesoporous template (dSi); b. one-layer oil phase assembly (dSi / IO1); c. two-layer oil phase assembly (dSi / IO2); d. three-layer oil phase assembly (dSi / IO3); e. four-layer oil phase assembly (dSi / IO4); f. pomegranate structured magnetic beads (SIS).
[0079] The SIS magnetic beads prepared in Example 1 were suspended in water and fully dispersed. The suspension was tested for hydrated particle size and polydispersity coefficient distribution using a Zetasizer Nano-ZS90 nano-laser particle size analyzer produced by Malvern, UK, and the absorbance was tested using a TU-1900 double-beam UV-visible spectrophotometer produced by Beijing Puxi Company, China. Then, magnetic separation was performed, the supernatant was removed by suction, and then water was added again to disperse the suspension by vibration, and the test was performed again.
[0080] Following the above steps, the SIS magnetic beads were resuspended in water (i.e., suspended and magnetically separated) 7 times at a concentration of 2 mg / mL and the hydrated particle size and polydispersity distribution were tested. The results are shown in Figure 6a , which also shows a photograph of the dispersion of SIS magnetic beads resuspended 7 times.
[0081] The magnetic capture efficiency and absorbance of the resuspension solution of SIS magnetic beads were tested by resuspending them in water (i.e., suspension-magnetic separation) 7 times at a concentration of 2 mg / mL. The results are shown in Figure 6b , which also shows a photo of the supernatant after magnetic separation after SIS magnetic beads were resuspended 7 times. The magnetic capture efficiency is calculated by testing the absorbance value of the SIS magnetic beads suspended in water, then magnetically separating the magnetic beads with a magnetic stand, and testing the absorbance value of the supernatant. Magnetic capture efficiency = (absorbance value of the suspension solution - absorbance value of the supernatant) / absorbance value of the suspension solution * 100%.
[0082] Figure 6a It can be seen that the particle size and PDI did not change significantly after 7 cycles of magnetic separation and resuspension, proving that the magnetic beads can still maintain good dispersion after multiple magnetic separation and resuspension, proving that the magnetic beads can be reused for separation. Figure 6b The excellent magnetic properties and reusability of the magnetic beads have been demonstrated, providing a strong guarantee for their subsequent biochemical separation applications.
[0083] 7. Surface carboxylation process of silica layer:
[0084] 1 mL of ammonia and 40 μL of 3-aminopropyltriethoxysilane (APTES) were added to 4 mL of the ethanol solution of SIS obtained in step 6 (containing about 5 mg of SIS), and the mixture was stirred at room temperature for 12 hours to obtain amino-modified SIS-NH2. The solid product was collected by centrifugation, and then the product was washed with ethanol to remove excess APTES and dispersed in 20 mL of N,N-dimethylformamide (DMF). 100 mg of succinic anhydride was added and stirred for 4 hours to obtain carboxyl-modified SIS microspheres (SIS-COOH). The solid product was collected by centrifugation, washed with ethanol and water several times, and finally dispersed in PB buffer (pH=6.0, 0.01 mol / L) at a concentration of 1 mg / mL.
[0085] The oil phase Fe3O4 prepared in step 3, the four-layer assembly (dSi / IO4) prepared in step 5, and the carboxyl-modified SIS microspheres (SIS-COOH) prepared in step 7 were dispersed in water at a concentration of 2 mg / mL, and their hysteresis curves were shown in Figure 1. Figure 5 As shown, Figure 5 Photographs of aqueous dispersions of SIS-COOH in the absence (left) and presence (right) of a magnet are shown.
[0086] from Figure 5It can be seen that the coercive force and remanence of Fe3O4 particles, dSi / IO4 four-layer assembly and SIS-COOH magnetic beads are negligible, which indicates that the synthesized Fe3O4 particles have superparamagnetism. Therefore, the prepared Fe3O4 particles, dSi / IO4 four-layer assembly and SIS-COOH magnetic beads all have superparamagnetism. Figure 5 The saturation magnetization intensity of the prepared Fe3O4 particles, dSi / IO4 four-layer assembly and SIS-COOH magnetic beads can be seen, indicating that the synthesized magnetic beads have good magnetic responsiveness and can be quickly separated in a magnetic field.
[0087] Figure 5 shows that when a magnetic field is applied outside the magnetic bead solution, SIS-COOH uniformly dispersed in the solution can be easily and completely attracted by the external magnet.
[0088] 8. iSIS Assembly Process of Magnetic Bead Capture Probes for Chemiluminescent Immunoassay
[0089] Take 4 mL of SIS-COOH microsphere solution (containing 4 mg SIS-COOH), add 2 mg EDC and 4 mg Sulfo-NHS and shake at room temperature for 30 min to activate the carboxyl groups on the surface of SIS-COOH microspheres in the buffer. The activated magnetic beads were magnetically separated and redispersed in the same volume of PBS buffer (0.01 M, pH=7.4), and 50 μL of 1 mg / mL mouse anti-prolactin monoclonal antibody 1 (mAb1) was added to react at room temperature for 2 h, and then BSA with a final concentration of 10 mg / mL was added for blocking for 2 h. The product was washed twice with PBS buffer (0.01 M, pH=7.4), the magnetic beads were collected by magnetic separation, and dispersed in PBS buffer (0.01 M, pH=7.4, containing 0.5% BSA, 0.02% Tween) at a dispersion concentration of 0.5 mg / mL, and stored at 4 °C to obtain the prolactin immune capture probe.
[0090] Mouse anti-testosterone monoclonal antibody 1 (mAb1) was used to prepare testosterone immune capture probe in the same way.
[0091] The iSIS magnetic bead probe of the present invention is used for chemiluminescence detection. Figure 1B shown.
[0092] 9. Detection of prolactin by sandwich immunoassay
[0093] First, a series of prolactin solutions with different concentration gradients were prepared using PBS buffer (0.01 M, pH = 7.4) as the solvent. The prolactin concentration range was 0 uIU-6000 uIU / mL.
[0094] 100 μL of prolactin solution with different concentrations was added to 100 μL of PBS buffer containing 0.5 mg / mL iSIS magnetic beads, which is a prolactin immune capture probe. The solution was incubated at 25°C with shaking for 10 minutes, and 100 μL of 0.125 mg / mL acridinium ester-mouse anti-prolactin monoclonal antibody 2 (mAb2) was added. The solution was incubated at 25°C with shaking for 10 minutes. After the incubation, the solution was washed three times with washing buffer. After the magnetic beads were washed by magnetic separation, the beads were redispersed in 500 μL of PBS buffer (0.01 M, pH=7.4) to obtain the immune complex test solution. When the chemiluminescence detection was performed, 50 μL of 5 mM hydrogen peroxide and 100 μL of 1 mM sodium hydroxide solution were added to the immune complex test solution, and the chemiluminescence intensity value of the immune complex was measured using an automatic chemiluminescence immunoassay (Meikang Bio MS-i3080).
[0095] The concentration of prolactin was used as the horizontal axis, and the chemiluminescence value of the immune complex of the iSIS magnetic beads (prolactin immune capture probe) of Example 1 of the present invention was tested as the vertical axis to prepare a standard curve a. The results are shown in Figure 7B As shown in b, the fitted linear regression equation was calculated and the R² of the obtained linear regression equation was 0.992, which had a high accuracy and high accuracy. The detection limit of prolactin was 0.6 uIU / mL.
[0096] In addition, the chemiluminescence intensity value of the immune complex of commercial magnetic beads (purchased from Thermo Fisher) and prolactin was tested according to the above steps, the only difference being "replacing 100 μL of PBS buffer containing 0.5 mg / mL iSIS magnetic beads with 100 μL of PBS buffer containing 0.5 mg / mL commercial magnetic beads", and the other steps remained unchanged, thereby measuring the chemiluminescence value of the immune complex of the commercial magnetic beads. The concentration of prolactin was used as the horizontal axis, and the chemiluminescence value of the immune complex of the commercial magnetic beads was used as the vertical axis to prepare the standard curve b.
[0097] The prolactin solution sample was detected by sandwich immunoassay using commercial magnetic beads, and the prolactin concentration of the measured sample was calculated using the standard curve b, which was recorded as the concentration of the tested prolactin clinical sample, with this as the horizontal axis; the prolactin solution sample was detected by sandwich immunoassay using the iSIS magnetic beads (prolactin immune capture probe) of Example 1 of the present invention, and the prolactin concentration of the measured sample was calculated using the standard curve a, which was recorded as the magnetic beads-chemiluminescence measurement value, with this as the vertical axis, and a correlation fitting curve was drawn, and the results are shown in FIG. Figure 7BThis figure reflects the detection correlation between SIS magnetic beads and commercial magnetic beads. R²=0.984 shows that the detection performance is close to that of commercial magnetic beads, proving that SIS has excellent clinical detection performance.
[0098] 10. Detection of testosterone by competitive assay
[0099] First, a series of testosterone solutions with different concentration gradients were prepared using PBS buffer (0.01 M, pH = 7.4) as the solvent. The testosterone concentration range was 0-25 ng / mL.
[0100] 100 μL of testosterone solution of different concentrations was added to 100 μL of PBS buffer containing 0.5 mg / mL iSIS magnetic beads, which is a testosterone immune capture probe. 100 μL of 0.125 mg / mL acridinium ester-mouse anti-testosterone monoclonal antibody 2 (mAb2) solution was added and incubated in a shaker at 37°C for 18 minutes. After the incubation, the beads were magnetically separated and washed three times with washing buffer. After magnetic separation and washing, the beads were redispersed in 500 μL PBS buffer (0.01 M, pH=7.4) to obtain the immune complex test solution. When the chemiluminescence detection was performed subsequently, 50 μL of 5 mM hydrogen peroxide and 100 μL of 1 mM sodium hydroxide solution were added to the immune complex test solution, and the chemiluminescence intensity value of the immune complex was measured using an automatic chemiluminescence immunoassay (Meikang Bio MS-i3080).
[0101] The concentration of testosterone was used as the horizontal axis, and the iSIS magnetic beads (testosterone immune capture probe) of Example 1 of the present invention were tested for detecting testosterone by chemiluminescence competition method, and the luminescence intensity ratio B / B0 was used as the vertical axis, wherein the chemiluminescence intensity value of the iSIS magnetic beads after detecting different concentrations of testosterone was recorded as B (i.e., the detection group), and the chemiluminescence intensity value of the iSIS magnetic beads after detecting PBS buffer (0.01 M, pH = 7.4) without testosterone was recorded as B0 (i.e., the blank group), and a standard curve x was prepared. The results are shown in Fig. 7A As shown in a, the fitting regression curve was calculated, R²=0.997, the accuracy value was very high, and it had high accuracy. The detection limit of testosterone was 0.045 ng / mL.
[0102] In addition, the chemiluminescence intensity of the immune complex of commercial magnetic beads (purchased from Thermo Fisher) and testosterone was tested according to the above steps. The only difference was that "100 μL of PBS buffer containing 0.5 mg / mL iSIS magnetic beads was replaced with 100 μL of PBS buffer containing 0.5 mg / mL commercial magnetic beads", and the other steps remained unchanged. The chemiluminescence value of the immune complex of the commercial magnetic beads was thus measured. The concentration of testosterone was used as the horizontal axis, and the luminescence intensity ratio B / B0 of the commercial magnetic beads used to detect testosterone by chemiluminescence competition method was used as the vertical axis to prepare the standard curve y.
[0103] The testosterone solution sample was detected by competitive detection using commercial magnetic beads, and the testosterone concentration of the sample was calculated using the standard curve y, which was recorded as the concentration of the testosterone clinical sample tested, with this as the horizontal axis; the testosterone solution sample was detected by competitive detection using the iSIS magnetic beads (testosterone immune capture probe) of Example 1 of the present invention, and the testosterone concentration of the sample was calculated using the standard curve x, which was recorded as the magnetic beads-chemiluminescence measurement value, with this as the vertical axis, and a correlation fitting curve was drawn, and the results are shown in FIG. Fig. 7A Figure b reflects the detection correlation between SIS magnetic beads and commercial magnetic beads. R²=0.993 shows that the detection performance is close to that of commercial magnetic beads, proving that SIS has excellent clinical detection performance.
[0104] in Figure 7A-7B The commercial magnetic beads here refer to the commercial Thermo Fisher Dynabeads™ MyOne™ 1 μm magnetic beads, which are available from Thermo Fisher Scientific. Example 2
[0105] The preparation steps of the magnetic particle nano-microsphere composite material SIS are repeated in Example 1, except that:
[0106] 1) In the operation steps of a single-layer assembly of magnetic particles, the amount of oil-phase iron oxide used ranges from 1 mg to 9 mg, so that the magnetic particle feed ratio ranges from 20% to 180%. Other operating conditions remain unchanged, and finally a series of single-layer assemblies (dSi / IO1) under different magnetic particle feed ratios are obtained.
[0107] 2) Using the one-layer assembly (dSi / IO1) prepared under the condition of 180% magnetic particle feeding ratio, the two-layer assembly operation of magnetic particles was continued. The amount of oil-phase iron oxide used ranged from 1 mg to 9.5 mg, so that the magnetic particle feeding ratio ranged from 20% to 190%. Other operating conditions remained unchanged, and finally a series of two-layer assemblies (dSi / IO2) under different magnetic particle feeding ratios were obtained.
[0108] 3) Using the two-layer assembly (dSi / IO2) prepared under the condition of 190% magnetic particle feeding ratio, the three-layer assembly operation of magnetic particles was continued. The amount of oil-phase iron oxide used ranged from 1 mg to 8 mg, so that the magnetic particle feeding ratio ranged from 20% to 160%. Other operating conditions remained unchanged, and finally a series of three-layer assemblies (dSi / IO3) under different magnetic particle feeding ratios were obtained.
[0109] 4) The three-layer assembly (dSi / IO3) prepared under the condition of 160% magnetic particle feeding ratio was used to continue the four-layer assembly of magnetic particles. The amount of oil-phase iron oxide used ranged from 1 mg to 6 mg, so that the magnetic particle feeding ratio ranged from 20% to 120%. Other operating conditions remained unchanged, and finally a series of four-layer assemblies (dSi / IO4) under different magnetic particle feeding ratios were obtained.
[0110] During the above-mentioned one to four-layer assembly process, the performance tests were performed on the assemblies prepared under different magnetic particle feeding ratios. The test method steps are as follows:
[0111] 1) Suspend the assembly in toluene solvent at 2 mg / mL. See the attached photo of the assembly suspension stock solution. Figure 4b The lower part of the sample was then tested for absorbance of the assembly suspension stock solution.
[0112] 2) Centrifuge the assembly suspension stock solution. See the attached photo of the supernatant after centrifugation. Figure 4b The upper part of the sample was then tested for absorbance of the supernatant.
[0113] The magnetic particle loading ratio in the assembly = (absorbance of the assembly suspension solution - absorbance of the supernatant after centrifugation) / absorbance of the assembly suspension solution * magnetic particle feeding ratio * 100%.
[0114] The corresponding relationship between the magnetic particle loading ratio and the magnetic particle feeding ratio in the assembly is shown in the attached Figure 4a For photos of the supernatant and the dispersion of the assembly during the first to fourth layer assembly process, see the attached Figure 4b .
[0115] from Figure 4a-4b It can be seen that the load capacity in the first-layer assembly stage (the ratio of the mass of the magnetic particles loaded on the template to the mass of the template) increases with the increase in the amount of magnetic particles added. The load limits that the magnetic particles can almost reach when assembling the first, second, third, and fourth layers correspond to magnetic particle feeding ratios of 180%, 190%, 160%, and 120%, respectively.
[0116] Figure 4bIt shows that as the loading amount of magnetic particles increases, the assembly solution of the one-layer assembly is dispersed in toluene in brown, while the supernatant changes from colorless to black. From the two-layer assembly, it can be seen that after the introduction of the PDA polymer, the assembly solution is dispersed in toluene in brown, and the supernatant also changes from colorless to black. From the three-layer assembly, it can be seen that after the introduction of the PDA polymer, the assembly solution is dispersed in toluene in brown, while the supernatant changes from colorless to black. From the four-layer assembly, it can be seen that after the introduction of the PDA polymer, the assembly solution is dispersed in toluene in brown, while the supernatant changes from colorless to black. This shows the successful loading of the magnetic particles.
[0117] In addition, it can be seen from the assembly results of the first to fourth layers that PDA filling is important for increasing the loading capacity of IOs. Example 3
[0118] The preparation steps of the magnetic particle nano-microsphere composite material SIS are repeated in Example 1, except that:
[0119] 1) In the operation steps of a single-layer assembly of magnetic particles, the amount of oil-phase iron oxide used ranges from 1 mg to 9 mg, so that the magnetic particle feed ratio ranges from 20% to 180%. Other operating conditions remain unchanged, and finally a series of single-layer assemblies (dSi / IO1) under different magnetic particle feed ratios are obtained.
[0120] 2) The one-layer assembly (dSi / IO1) prepared under the condition of 180% magnetic particle feeding ratio was used to continue the operation of two-layer assembly of magnetic particles. The differences were the following two points: first, "0.56 mL PDA ethanol solution (10 mg / mL)" was replaced by "0.56 mL PEI (average molecular weight 1800) ethanol solution (10 mg / mL)"; second, the amount of oil phase iron oxide was in the range of 1 mg to 6 mg, so that the magnetic particle feeding ratio ranged from 20% to 120%. Other operating conditions remained unchanged, and finally a series of two-layer assemblies (dSi / IO2) under different magnetic particle feeding ratios were prepared.
[0121] 3) The two-layer assembly (dSi / IO2) prepared under the condition of 120% magnetic particle feeding ratio was used to continue the operation of three-layer assembly of magnetic particles. The differences were the following two points: first, "0.56 mL PDA ethanol solution (10 mg / mL)" was replaced by "0.56 mL PEI (average molecular weight 1800) ethanol solution (10 mg / mL)"; second, the amount of oil phase iron oxide was in the range of 1 mg to 6 mg, so that the magnetic particle feeding ratio ranged from 20% to 120%. Other operating conditions remained unchanged, and finally a series of three-layer assemblies (dSi / IO3) under different magnetic particle feeding ratios were obtained.
[0122] 4) The three-layer assembly (dSi / IO3) prepared under the condition of 120% magnetic particle feeding ratio was used to continue the operation of four-layer assembly of magnetic particles. The differences were as follows: first, "0.56 mL PDA ethanol solution (10 mg / mL)" was replaced by "0.56 mL PEI (average molecular weight 1800) ethanol solution (10 mg / mL)"; second, the amount of oil-phase iron oxide was in the range of 1 mg to 5 mg, so that the magnetic particle feeding ratio ranged from 20% to 100%. Other operating conditions remained unchanged, and finally a series of four-layer assemblies (dSi / IO4) under different magnetic particle feeding ratios were obtained.
[0123] 5) The four-layer assembly (dSi / IO4) prepared under the condition of 100% magnetic particle feed ratio was used to continue the operation of five-layer assembly of magnetic particles. The specific operation was as follows: the four-layer assembly precipitate was taken, blown dry, 0.56 mL of PEI (average molecular weight 1800) ethanol solution (10 mg / mL) was added to the assembly for ultrasonic dispersion, ultrasonic for 5 min, then washed once with ethanol and blown dry. Iron oxide dispersed in toluene was taken separately, the amount of oil phase iron oxide ranged from 1 mg to 5 mg, so that the magnetic particle feed ratio ranged from 20% to 100%, added to the assembly silicon sphere, ultrasonically mixed for 7 minutes, centrifuged, and the supernatant was removed to obtain the precipitate, which was the five-layer assembly (dSi / IO5).
[0124] During the above-mentioned one to five-layer assembly process, the performance tests were performed on the assemblies prepared under different magnetic particle feeding ratios. The test method steps are as follows:
[0125] 1) Suspend the assembly in toluene solvent at 2 mg / mL. See the attached photo of the assembly suspension stock solution. Figure 8 The lower part of the assembly suspension was then tested for absorbance.
[0126] 2) Centrifuge the assembly suspension stock solution. See the attached photo of the supernatant after centrifugation. Figure 8 The upper part of the supernatant was then tested for absorbance.
[0127] The corresponding relationship between the magnetic particle loading ratio and the magnetic particle feeding ratio in the assembly is shown in the attached Fig. 9 It can be seen from the figure that the load capacity in the first-layer assembly stage (the ratio of the mass of the magnetic particles loaded on the template to the mass of the template) increases with the increase of the amount of magnetic particles added. The load limit that the magnetic particles can almost reach when assembling the first, second, third, fourth and fifth layers corresponds to the magnetic particle feeding ratio of 180%, 120%, 120%, 100% and 100%, respectively.
[0128] Attached Figure 8It shows that as the loading amount of magnetic particles increases, the assembly solution of the first-layer assembly is dispersed in toluene as brown, while the supernatant changes from colorless to black. From the two-layer assembly, it can be seen that after the introduction of PEI (molecular weight 1800), the assembly solution is dispersed in toluene as brown, and the supernatant also changes from colorless to black. From the three-layer assembly, it can be seen that after the introduction of PEI (molecular weight 1800), the assembly solution is dispersed in toluene as brown, while the supernatant changes from colorless to black. From the four-layer assembly, it can be seen that after the introduction of PEI (molecular weight 1800), the assembly solution is dispersed in toluene as brown, while the supernatant changes from colorless to black. From the five-layer assembly, it can be seen that after the introduction of PEI (molecular weight 1800), the assembly solution is dispersed in toluene as brown, while the supernatant changes from colorless to black. This shows the successful loading of magnetic particles.
[0129] According to the experimental results of Examples 2 and 3 of the present invention, the microspheres prepared by filling with PDA have a higher loading efficiency for oil-phase iron oxide.
[0130] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.
Claims
1. A method for preparing templated ligand-driven assembly-type pomegranate-like structured immunomagnetic beads, characterized in that Using dendritic mesoporous silica dSi as a template, an affinity dopamine-modified silane reagent with a catechol group at the end is grafted into the pores of the dSi template to form a high-affinity surface, providing binding sites for the dense assembly of the first layer of magnetic particles, thereby obtaining a dendritic silicon template modified by the catechol group, and then the first layer of oil-phase magnetic particles IOs are assembled on the template, and then the dopamine-grafted polymer PDA or PEI is used as a mediator to make the polymer PDA or PEI and the oil-phase magnetic particles IOs have a layer-by-layer affinity in an organic solvent. Assemble them onto a silicon template to achieve layer-by-layer assembly of oil-phase magnetic particles IOs, so that multiple layers of IOs are assembled on the silicon template. Then, octyltrimethoxysilane (OTMS) is used to undergo a hydrolysis and condensation reaction on the surface of the microsphere assembly to achieve a phase transfer of the microsphere assembly from the organic phase to the aqueous phase. Then, tetraethyl orthosilicate (TEOS) is hydrolyzed to grow a thin layer of silica through the Stöber method to improve the stability of the microsphere assembly. Then, 3-aminopropyltriethoxysilane is used to perform amino modification, and succinic anhydride is used to perform carboxyl modification to obtain carboxylated magnetic beads.
2. The method for preparing a templated ligand-driven assembly-type pomegranate-like structured immunomagnetic beads according to claim 1, characterized in that The preparation method of the affinity dopamine-modified silane reagent with a catechol group at the end comprises the following steps: adding dopamine and dihydro-3-[3-(triethoxysilyl)propyl]furan-2,5-dione to anhydrous DMF, ultrasonically homogenizing, and stirring at a speed of 100-250 rpm for 15-20 h at room temperature to obtain the dopamine-modified silane reagent; wherein the molar ratio of dopamine to dihydro-3-[3-(triethoxysilyl)propyl]furan-2,5-dione is 1.5-3:
1.
3. The method for preparing a templated ligand-driven assembly-type pomegranate-like structured immunomagnetic beads according to claim 1, characterized in that The preparation method for grafting an affinity dopamine-modified silane reagent onto a dSi template comprises the following steps: adding the dSi template and the affinity dopamine-modified silane reagent into ethanol, and adding ammonia water to adjust the solution to be alkaline, and the resulting mixture should be stirred and reacted at room temperature for 10-15 hours, wherein the ratio of the amount of the catechol group component in the affinity dopamine-modified silane reagent to the mass of the dSi template is 0.01-0.03:1, the unit of the amount of the substance is mmol, and the unit of mass is mg.
4. The method for preparing a templated ligand-driven assembly-type pomegranate-like structured immunomagnetic beads according to claim 1, characterized in that The preparation method of the dopamine-grafted polymer PDA comprises the following steps: Step 1: Under nitrogen protection, poly(isobutylene-maleic anhydride) was heated and dissolved in DMF solvent; Step 2: dopamine hydrochloride is dissolved in DMF solvent, triethylamine is added, and the molar ratio of triethylamine to dopamine hydrochloride is 1-1.5:
1. The solution becomes turbid, and is stirred at room temperature for 1-3 hours under a nitrogen atmosphere to activate dopamine, and then the formed triethylamine hydrochloride is removed by centrifugation to obtain a supernatant; Step 3: Add the supernatant of step 2 dropwise to the solution of step 1, stir overnight at 60-80°C, remove DMF under vacuum, add deionized water to precipitate the product, wash with 0.5-2 M hydrochloric acid solution, then rinse with deionized water, freeze-dry the solution, and the product is a white powder; The mass ratio of the poly(isobutylene-maleic anhydride) in step 1 to the dopamine hydrochloride in step 2 is 1.5-3:
1.
5. The method for preparing a templated ligand-driven assembly-type pomegranate-like structured immunomagnetic beads according to claim 1, characterized in that The first layer of load assembly of oil-phase magnetic particles IOs is carried out on the dendritic silicon template modified by catechol groups, and the process is as follows: take a toluene solution of oil-phase magnetic particles IOs, add the dendritic silicon template modified by catechol groups, ultrasonicate for 3-10 minutes to obtain a uniform mixed solution, then collect the precipitated product by centrifugation, and after the residual toluene solvent in the precipitate evaporates, a layer of IOs assembly dSi / IO1 is obtained; the mass ratio of the template to the oil-phase magnetic particles IOs is 1:1.5-2.
0.
6. The method for preparing a templated ligand-driven assembly type pomegranate-like structured immunomagnetic beads according to claim 1, characterized in that When assembling multiple layers of IOs on the silicon template, the assembly operation of each layer of IOs includes the following two steps: S1 assembling and filling polymer PDA or PEI: adding an ethanol dispersion of polymer PDA or PEI to the upper layer assembly, wherein the mass ratio of the silicon template to the polymer PDA or PEI in the assembly is 1:0.5-2, performing ultrasonic dispersion, then collecting the precipitated product by centrifugation, and washing with ethanol to obtain an intermediate layer assembly filled with PDA or PEI; S2 performs the next layer assembly of IOs: adding the toluene solution of oil phase magnetic particles IOs to the intermediate layer assembly filled with PDA or PEI obtained in step S1, ultrasonicating for 3-10 minutes to obtain a uniform mixed solution, and then collecting the precipitated product by centrifugation to obtain the next layer assembly of IOs; wherein the mass ratio of the silicon template in the intermediate layer assembly filled with PDA or PEI to the oil phase magnetic particles IOs is 1:1-2; Repeat the above steps S1-S2 1-4 times to assemble a total of 2-5 layers of oil phase magnetic particles 10s.
7. A templated ligand-driven assembly type pomegranate-like structured immunomagnetic beads prepared by the method according to any one of claims 1 to 6.
8. The use of a templated ligand-driven assembly type pomegranate-like structure immunomagnetic bead in the preparation of a chemiluminescent detection reagent as claimed in claim 7, characterized in that The method comprises an assembly process of a magnetic bead capture probe iSIS, wherein the magnetic bead capture probe iSIS comprises a prolactin immune capture probe or a testosterone immune capture probe; The assembly process of the prolactin immune capture probe comprises the following steps: adding the immunomagnetic beads, i.e., carboxyl-modified microsphere assembly, to a pH=6.0 PB buffer, adding Sulfo-NHS and EDC, and incubating in a shaker for 20-40 min; then collecting the product by centrifugation; resuspending the product in a pH=7.4 PBS buffer, adding a mouse anti-prolactin monoclonal antibody 1, reacting at room temperature for 2-3 h, and then adding a final concentration of 5-20 mg / mL BSA for blocking for 1.5-3 h; then collecting the microspheres by centrifugation, counting them as iSIS magnetic beads, washing them with a pH=7.4 PBS buffer, and storing them in a pH=7.4 PBS buffer for refrigeration; and preparing a testosterone immune capture probe in the same manner using a mouse anti-testosterone monoclonal antibody 1; The magnetic bead capture probe iSIS utilizes chemiluminescent immunoassay technology to analyze and detect prolactin or testosterone.
9. The use according to claim 8, characterized in that It involves measuring prolactin by sandwich immunoassay, as follows: Step 1: Prepare a series of prolactin solutions with different concentration gradients, with the prolactin concentration range being 0 uIU / mL-6000uIU / mL; Step 2: The prolactin solutions of different concentrations prepared in step 1 are mixed with pH=7.4 PBS buffer containing iSIS magnetic beads, respectively, and incubated by shaking, and then acridinium ester-mouse anti-prolactin monoclonal antibody 2 is added, and the shaking incubation is continued, and then the product is separated by magnetic separation, and the product is washed with pH=7.4 PBS buffer, and then redispersed in pH=7.4 PBS buffer, and hydrogen peroxide with a final concentration of 0.4-1.0 mM and sodium hydroxide with a final concentration of 0.1-0.3 mM are added thereto, and the chemiluminescence intensity value of the immune complex is measured by a chemiluminescence immunoassay; the concentration of prolactin is used as the horizontal axis, and the chemiluminescence value of the immune complex of the iSIS magnetic beads is tested as the vertical axis, and a standard curve is prepared, and a linear regression equation is obtained by fitting; The iSIS magnetic beads are prolactin immune capture probes; Step 3: When testing the prolactin solution sample, the prolactin solution sample, pH=7.4 PBS buffer containing iSIS magnetic beads, and acridinium ester-mouse anti-prolactin monoclonal antibody 2 are oscillated and incubated according to the test method of step 2, followed by magnetic separation and washing, and then redispersed in pH=7.4 PBS buffer. The chemiluminescence intensity value of the immune complex is measured by a chemiluminescence immunoassay instrument, and the value is substituted into the linear regression equation obtained in step 2 to infer the prolactin content in the prolactin solution sample.
10. The use according to claim 8, characterized in that The testosterone test is performed by a competitive assay, the process is as follows: Step 1: Prepare a series of testosterone solutions with different concentration gradients, with the testosterone concentration range being 0-25 ng / mL; Step 2: Testosterone solutions of different concentrations are mixed with pH=7.4 PBS buffer containing iSIS magnetic beads, acridinium ester-mouse anti-testosterone monoclonal antibody 2 is added and incubated by shaking, and then the product is separated by magnetic separation, and the product is washed with pH=7.4 PBS buffer, and then redispersed in pH=7.4 PBS buffer, and hydrogen peroxide with a final concentration of 0.4-1.0mM and sodium hydroxide with a final concentration of 0.1-0.3mM are added thereto, and the chemiluminescence intensity value of the immune complex is measured by a chemiluminescence immunoassay; the chemiluminescence intensity value of the iSIS magnetic beads after detecting different concentrations of testosterone is recorded as B, and a blank group is set up, and the chemiluminescence intensity value of the iSIS magnetic beads after detecting pH=7.4 PBS buffer without testosterone is recorded as B0, and the concentration of testosterone is used as the horizontal coordinate, and the chemiluminescence intensity ratio B / B0 is used as the vertical coordinate, and a standard curve is prepared, and a regression curve is fitted; the iSIS magnetic beads are testosterone immune capture probes; Step 3: When testing the testosterone solution sample, the testosterone solution sample, pH=7.4 PBS buffer containing iSIS magnetic beads, and acridinium ester-mouse anti-testosterone monoclonal antibody 2 are oscillated and incubated according to the test method of step 2, followed by magnetic separation and washing, and then redispersed in pH=7.4 PBS buffer. The chemiluminescence intensity value B1 of the immune complex is measured using a chemiluminescence immunoassay instrument, and the chemiluminescence intensity ratio B1 / B0 is calculated and substituted into the regression curve obtained in step 2 to infer the testosterone content in the testosterone solution sample.
Citation Information
Patent Citations
Magnetic poly-dopamine-iron oxide nanoparticles and preparation method thereof
CN102034584A
Specific L-serine aptamer and application thereof
CN105821046A